Clinical profile of atrial fibrillation in hospitalized patients: experience from two tertiary centers of Bangladesh - Islam, A K M Monwarul; Shimu, Ishrat Jahan; Rahman, Mohammad Arifur; Wareshuzzaman, Md; Rahman, Muhammad Saidur; Ananya, Kaniz Fatema; Islam, Md Nazmul; Abdullah, Muhammad; Mehfuz E Khoda, Mohammad; Zaman, Shahana (BIRDEM Medical Journal, 2023)
Background: Chronic rheumatic heart disease (RHD), particularly mitral stenosis, is traditionally thought to be the dominating cause of atrial fibrillation (AF) in Bangladesh. But over the past decades, parallel to the changes in dominating disease pattern, rheumatic fever and possibly RHD has declined in the country. Also, the current practice of anticoagulation in AF here is not known. The study was carried out to explore the current aetiology and clinical profile of AF in hospitalized patients. Methods: This cross-sectional study included 302 consecutive adult patients with AF admitted in 2 hospitals in Dhaka, Bangladesh. History, clinical examination and investigations including transthoracic echocardiography were done to find out the aetiology, type of AF, selected complications and the pharmacotherapy including anticoagulation practice in hospitalized AF patients. Results: The mean age of the patients was 54.00 ± 12.46 years (range 14 to 85 years). The most common etiology was rheumatic valvular heart disease (47.7%), followed by ischaemic heart disease (IHD) (29.5%) and hypertensin (5.0%). Majority (249, 82%) had coarse AF and only 18% had fine AF. Thirteen (4.3%) patients presented with stroke and 7 (2.3%) had left atrial thrombus. The most common drugs used were beta blocker (32.78%), digoxin (32.45%) and combination of beta blocker and digoxin (23.84%). Anticoagulant was used in 56.95% cases. Among the anticoagulants, warfarin was most commonly prescribed (69.18%), followed by rivaroxaban and apixaban in 15.69% and 13.95% cases, respectively. Conclusion: RHD is still the dominating cause of AF in hospitalized patients in Bangladesh. Despite high prevalence of rheumatic valvular AF, anticoagulants are underused. Warfarin is far more commonly used than the direct oral anticoagulants (DOACs). BIRDEM Med J 2023; 13(3): 143-148